The key management of direct/external modulation semiconductor laser response systems for relative intensity noise control - Mahmoud M. A. Eid; Ashraf S. Seliem; Ahmed Nabih Zaki Rashed; Abd El-Naser A. Mohammed; Mohamed Yassin Ali; Shaimaa S. Abaza (Institute of Advanced Engineering and Science, 2021)
This study outlines the management of either direct or external modulation semiconductor laser systems for the key solution of bit rate up to 25 Gb/s under relative intensity noise (RIN) control. The bias and modulation peak currents based laser rate equations are optimized to achieve max Q factor and min bit error rate (BER) using first proposed model and optical/electrical signal power, optical/electrical signal to noise ratio are also enhanced using second proposed model. The percentage enhancement ratio in max. Q-factor and min. BER using first proposed model ranges from 53.25 % to 71.63 % in compared to the previous model. In the same way, by using second proposed model, the electrical signal power at optical receiver is enhanced within the range of 48.66 % to 68.88 % in compared to the previous model. Optical signal/noise ratio (OSNR) after optical fiber cable (OFC), signal/noise ratio (SNR) after electrical filter are measured with using different electrical pulse generators and electrical modulators at the optimization stage. The first proposed model reported better max. Q and min. BER values than the previous model. In addition to the second proposed model (direct modulation) has outlined better optical/electrical signal power than the previous model, while max. Q, min. BER values are kept constant. It is found that non return to zero pulse generator has presented better signal power than other pulse generators by using second proposed model. As well as the mixed of raised cosine pulse generator with external modulator reported max. Q, min. BER with other pulse generators by using first proposed model. OSNR at OFC is optimized by using continuous phase frequency shift keying (CPFSK) electrical modulator, While SNR at optical receiver is optimized by using phase shift keying (PSK) electrical modulator.